Penerapan Inquiry-Based Learning (IBL) dalam Pembelajaran Matematika China dan Drill and Practice Indonesia di Sekolah Dasar Jakarta International School - Sriyono, Sriyono; Susanti, L. R Retno; Hudaidah, Hudaidah; Yadi, Farhan (FONDATIA, 2024)
In Indonesia, many elementary schools still rely on the Drill and Practice method, which focuses on repetitive exercises to strengthen students' basic mathematical skills. While effective for honing technical abilities like calculations and formula application, this method does not foster the development of complex critical and creative thinking. In contrast, China has adopted an Inquiry-Based Learning (IBL) approach in mathematics education, which emphasizes critical thinking, problem-solving, and exploration through questioning. This study aims to examine the effectiveness of IBL in comparison to Drill and Practice, particularly in terms of its impact on student learning outcomes in both China and Indonesia. Using a quantitative approach with experimental design, the study compares the implementation of IBL in China with the Drill and Practice method at Jakarta International School (JIS). The results show that IBL in China significantly enhances students' higher-order thinking skills, particularly in problem-solving, critical thinking, and creativity. Students in the IBL group in China demonstrated a greater improvement in their test scores compared to the control group at JIS. The post-test average for the IBL group in China was 85.5, while the JIS group only reached 67.8. Additionally, 75% of IBL students in China were able to apply mathematical concepts to real-world situations, compared to just 45% at JIS. Moreover, IBL students in China reported higher motivation and engagement, with 78% feeling more motivated to study, compared to only 50% at JIS. Furthermore, 72% of IBL students in China used multiple methods to solve problems, in contrast to 40% at JIS. Statistical analysis confirmed these findings, with a significant t-value of 4.35 and a p-value of 0.005, supporting the effectiveness of IBL in fostering critical thinking and creativity.